El ejercicio físico y su prescripción en pacientes con enfermedades crónicas degenerativas - Gómez, Rossana [UNESP] (2010)
Chronic degenerative diseases constitute one of the main causes of death at a global level, and their significant increase has alerted many countries, which are taking measures to reduce risk factors, some of which are modifiable; being the regular exercise a means of prevention and rehabilitation of these diseases. The objective of this revision is to analyze the necessary parameters to take into account for the prescription of an exercise program in patients with obesity, high blood pressure dyslipidemia and diabetes mellitus type 2.